2020
DOI: 10.3390/app10207129
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Energy Certification on Housing Sales Prices in the Province of Alicante (Spain)

Abstract: This work examines the implementation of energy labelling by the residential real estate sector. First, it considers the interest by real estate sellers in not publishing energy certification information, and then, it quantifies the impact of the housing’s energy certification on the asking price. The results are compared with those obtained from other studies conducted in distinct European countries. The study’s final sample was collected, including information from 52,939 multi-family homes placed on the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
1
9
0
1
Order By: Relevance
“…A study conducted in Germany showed that the age and size of a residential property have significant impacts on its rental value [73]. These results are consistent with those reported in Cespedes-Lopez's study [74], which showed that green features (such as green rating) do not influence the value of residential properties located in Alicante, Spain. Overall, the findings provide further support for the hypothesis that the size of residential properties is a good indicator of their value.…”
Section: Discussionsupporting
confidence: 84%
“…A study conducted in Germany showed that the age and size of a residential property have significant impacts on its rental value [73]. These results are consistent with those reported in Cespedes-Lopez's study [74], which showed that green features (such as green rating) do not influence the value of residential properties located in Alicante, Spain. Overall, the findings provide further support for the hypothesis that the size of residential properties is a good indicator of their value.…”
Section: Discussionsupporting
confidence: 84%
“…Li et al [249] investigated macroeconomic parameters that may affect real estate prices and designed a prediction model for price fluctuation. The energy effects on house pricing were investigated by Cespedes-Lopez et al [250]. They confirmed that qualifications for energy have an effect on the asking price of housing.…”
Section: House Pricing and Affordabilitymentioning
confidence: 90%
“…Cespedes-Lopez et al [53], Chegut et al [54], Wilhelmsson [55], Graaf [56], Cerin et al [57], Högberg [58], and Fuerst and McAllister [59]. However, this literature review highlights the lack of consensus regarding the impact of EPCs on transaction prices and rents.…”
Section: Concerns About Transaction Prices and Rentsmentioning
confidence: 96%
“…However, this literature review highlights the lack of consensus regarding the impact of EPCs on transaction prices and rents. While some authors suggest that EPCs lead to an increase in transaction prices and rents (e.g., Mudgal et al [7]; McCord et al [26]; Barreca et al [50]; Khazal and Sønstebø, [51]; Chegut et al [54]; Graaf, [56]; Cerin et al [57]; and Högberg [58]), others suggest that they have no effect (e.g., McCord et al [52]; Cespedes-Lopez et al [53]; Chegut et al [54]; Wilhelmsson [55]; and Fuerst and McAllister [59]).…”
Section: Concerns About Transaction Prices and Rentsmentioning
confidence: 99%